Dampak Pembuangan Sampah terhadap Lingkungan Pesisir Pantai Putra Deli : Analisis Jenis Sampah Dominan - Sakira Putri Manurung; Habibatul Qolbi Sumardi; Dhio Febriansyah Lubis; Meilinda Suriani Harefa (Studi Administrasi Publik dan ilmu Komunikasi, 2025)
This study aims to find the most dominant type of waste that damages the coastal area of ​​Putra Deli Beach, Deli Serdang Regency. Based on field observations and interviews with local people, it was found that inorganic, including plastic, is the type of waste that damages the coastal environment the most. Plastic waste persists such as beverage bottles, plastic bags, styrofoam, and food wrappers which are dominant because they do not decompose quickly. This condition is exacerbated by the low public awareness in maintaining cleanliness and the lack of adequate waste management facilities. The impact is not only visually polluting the environment, but also threatening the marine ecosystem, public health, and reducing the value of local tourism. The results of this study are expected to be the basis for mitigation efforts and improving waste management in coastal areas.